Utilization of QR Code for Tracking Digital Expenses - Gerardo Axel Lwiantoro; Farhan Putra Salsabil; Gregorius A. N. Aditantyo; Derwin Suhartono (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
Today, a lot of us have a lot of digital wallet services that we use. Because of that tracking our spending has become significantly harder because most people use more than one digital wallet. This study aims to find out how can we utilize QR code in the payment receipt at out digital transaction, to keep track on our transaction on various digital wallet. To help keep track of the expenses from the various digital wallet, we use QR code that is generated from the receipt of the transaction that contain the encrypted data of the transaction that occurs. This data can be scanned so it can be added to a personal budget tracker app so the user can manage their digital expenses in one view.